DIAGNOSIS OF GASTROINTESTINAL FOREIGN BODIES IN THE CANINE THROUGH ULTRASONOGRAPHY AND RADIOLOGY - Cahua U., Jacqueline (2009)
The aim of this study was to determine whether the technique of ultrasound or radiographic image diagnosis, better supports a probable diagnosis of gastrointestinal foreign body. Thirteen dogs with presumptive diagnosis of gastrointestinal obstruction were subjected to radiological tests and ultrasound evaluation. Ultrasonography showed the presence of foreign bodies in all 13 cases, while through radiology, three foreign bodies were identified and seven were suspected of foreign body obstruction due to the intestinal distension. The foreign bodies were sonographically identified by the distal acoustic shadow and various degrees of reflection produced on the surface. In addition, the thickening of the stomach and intestinal wall in some animals, and free peritoneal fluid in a patient could be observed through ultrasound images. The findings in this study suggest that ultrasound can be used for the diagnosis of gastrointestinal foreign bodies in small animals with a likely gastrointestinal obstruction, and may be more appropriate than radiology.